Silicone Orbital Prosthesis: A Case Report on Prosthetic Rehabilitation of Orbital Exenteration - Shrestha, Amita; Sapkota, Binam (Journal of Nepalese Prosthodontic Society, 2025)
The fabrication of an adhesive-retained silicone orbital prosthesis offers an economical and esthetic solution for patients with orbital defects, resulting from neoplastic disorders or extensive facial trauma. This prosthetic design eliminates the need for complex surgical implant therapy or mechanical retention, ensuring a more comfortable and cost-effective treatment option. This case report outlines the step-by-step process involved in the fabrication of an adhesive-retained silicone orbital prosthesis, emphasizing on the material selection, techniques and clinical considerations.